Exploring creativity evaluative practices in innovation, design, and the arts - Moeran, Brian, 1944-; Christensen, Bo T.; ProQuest (Firm) (Cambridge : Cambridge University Press, 2013)
"Moeran and Christensen examine evaluative practices in the creative industries by exploring the processes surrounding the conception, design, manufacture, appraisal and use of creative goods. The book describes the editorial choices made by different participants in a 'creative world', as they go about conceiving, composing or designing, performing or making, selling and assessing a range of cultural products. The study draws upon ethnographically rich case studies from companies as varied as Bang and Olufsen, Hugo Boss and Lonely Planet, in order to reveal the broad range of factors guiding and inhibiting creative processes. Some of these constraints are material and technical; others social or defined by aesthetic norms. The authors explore how these various constraints affect creative work and how ultimately they contribute to the development of creativity"--
Machine generated contents note: Preface Howard S. Becker; Introduction Brian Moeran and Bo T. Christensen; 1. What's the matter with Jarrettsville? Genre classification as an unstable and opportunistic construct C. Clayton Childress; 2. In search of a creative concept in Hugo Boss Kasper T. Vangkilde; 3. Reconceiving constraint as possibility in a music ensemble Shannon O'Donnell; 4. The Ursula faience dinnerware series by Royal Copenhagen Brian Moeran; 5. Looking into the box: design and innovation at Bang and Olufsen Jakob Krause-Jensen; 6. Creativity in the brief: travel guidebook writers and good work Ana Alacovska; 7. Celebrity status, names and ideas in the advertising award system Timothy de Waal Malefyt; 8. Evaluation in film festival prize juries Chris Mathieu and Marianne Bertelsen; 9. Restaurant rankings in the culinary field Bo T. Christensen and Jesper Strandgaard Pedersen; 10. Patina meets fashion: on the evaluation and devaluation of oriental carpets Fabian Faurholt Csaba and Guliz Ger; Afterword Keith Sawyer.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Creative ability in business; Technological innovations; Design; Organizational behavior; Electronic books